ENVIRONMENTAL CONDITIONS AS A RISK FACTOR FOR THE SPREAD OF ALLERGIC DISEASES IN KARAKALPAKSTAN - Kudaybergenova Ulbike Kallibekovna,; Aimurzaeva Lazzat Kuralbekovna,; Abdizemilova Shakhnoza Yakipbay qizi, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The article presents the results of a study of the prevalence of allergic diseases among the population of the Republic of Karakalpakstan. It is shown that the highest incidence of allergic rhinitis (immediate type allegopathology) is detected among the population of the III ecological group (northern zone) in areas with high aerogenic pollution - Kungrad, Muynak and Takhtakupyr regions.